2009
DOI: 10.1177/1557085109332352
|View full text |Cite
|
Sign up to set email alerts
|

Between Life and Death

Abstract: This study presents an analysis of the population and crimes of women in a state prison for women in Hyderabad, India. Women in India are disproportionately incarcerated for violent crimes, in particular, offenses related to dowry. Using qualitative data gathered from interviews with 49 women, the authors examine the context of their lives and their paths to prison. Ultimately, the authors make a case for an intersectional analysis, one that seeks to understand the lives of women in a matrix of inequalities sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Daly's (1994) framework has been reassessed and further developed by several western feminist researchers, utilising both quantitative and qualitative methodologies to map women's imprisonment trajectories (e.g., DeHart 2008; Simpson et al 2008), but gender comparative work is limited (see Daggett 2014;Jones et al 2014). Together, this work supports core facets of Daly's (1994) research, as do findings from research conducted beyond the Anglosphere, with areas of place-specific variance (e.g., for non-western studies that have considered interpersonal violence, see Artz et al 2012;Cherukuri et al 2009;Jeffries et al 2019;Russell et al 2020;Veloso 2016Veloso , 2022 Additionally, limited access to justice, and an inability to negotiate corrupted criminal legal systems, have been identified as contributing to women's criminalisation in Southeast and East Asia (e.g., Cherukuri et al 2009;Jeffries and Chuenurah 2018;Veloso 2016Veloso , 2022. Finally, and of more specific background relevance here, there are three previous studies conducted in Southeast Asia that have either included Smart 1977).…”
Section: Feminist Pathwayssupporting
confidence: 69%
“…Daly's (1994) framework has been reassessed and further developed by several western feminist researchers, utilising both quantitative and qualitative methodologies to map women's imprisonment trajectories (e.g., DeHart 2008; Simpson et al 2008), but gender comparative work is limited (see Daggett 2014;Jones et al 2014). Together, this work supports core facets of Daly's (1994) research, as do findings from research conducted beyond the Anglosphere, with areas of place-specific variance (e.g., for non-western studies that have considered interpersonal violence, see Artz et al 2012;Cherukuri et al 2009;Jeffries et al 2019;Russell et al 2020;Veloso 2016Veloso , 2022 Additionally, limited access to justice, and an inability to negotiate corrupted criminal legal systems, have been identified as contributing to women's criminalisation in Southeast and East Asia (e.g., Cherukuri et al 2009;Jeffries and Chuenurah 2018;Veloso 2016Veloso , 2022. Finally, and of more specific background relevance here, there are three previous studies conducted in Southeast Asia that have either included Smart 1977).…”
Section: Feminist Pathwayssupporting
confidence: 69%
“…The demographic profile of respondents revealed that most of them came from poor backgrounds. Data on socioeconomic status corroborated similar findings by Cherukuri, Britton, and Subramaniam (2009); Kaushik and Sharma (2009); and Shankardass (2012Shankardass ( , 2000 that most of the imprisoned women in India came from low-income families.…”
Section: Study Sites and Participantssupporting
confidence: 63%
“…Close to 75 per cent of women in the prison are in the age groups of 18–45 years. A 2006 study undertaken in SPW documented the presence of 52 women indicating a sixfold increase in the prison population of women over 12 years (Cherukuri et al, 2009). In the late 1990s and early 2000, Telangana prisons housed several political prisoners including women associated with the Naxalite movements.…”
Section: Women In Prisons: a Brief Profilementioning
confidence: 99%
“…In India, women account for about 5 per cent of the prison population. Women's prisons are usually extensions of the men's prisons and sometimes located within the same premises with independent amenities (Cherukuri et al, 2009;Ministry of Women Child and Development, 2018). Consequently, prison reform programmes for women's prison usually follow the same template designed and delivered with some success for men (Barberet & Jackson, 2017;Hannah-Moffat, 2010;Raghavan, 2014;Van Wormer, 2010).…”
mentioning
confidence: 99%